Membangun Kesadaran Spiritual untuk Kelestarian Alam: Arah Baru Eco-Teologi di Indonesia - Zahratul Faizah (Bansigom Na Publisher, 2026)
The current global ecological crisis is a manifestation of a profound spiritual crisis, where technocratic approaches often fail to address the root causes of human behavior. This study aims to map the new direction of eco-theology in Indonesia as an instrument for building spiritual awareness in nature conservation. Using a descriptive qualitative method with the Miles and Huberman interactive analysis model, this research explores the integration of Islamic principles such as Tauhid, Khalifah, and Mizan in environmental policies. Findings indicate that the transition from an exploitative masculine theology to a feminine theology based on compassion (Ar-Rahman and Ar-Rahim) is crucial in shifting societal paradigms. Implementation through the Eco-Pesantren movement and MUI's Green Fatwas has proven to provide strong moral legitimacy for conservation actions at the grassroots level. This study concludes that strengthening inclusive ecological spirituality is a prerequisite for ecosystem sustainability in Indonesia. Recommendations include the standardization of eco-theology curricula in religious education institutions and strengthening collaboration between religious authorities and government environmental agencies